Comprehensive Evaluation of the Transient Reactive Power Support Capability of New Energy Stations Based on TOPSIS. Issue 1 (1st January 2022) - Chang, Xiao; Zhang, Min; Zhao, Junyi; Yang, Chaoying; Liu, Yang; Fan, Rui; Guo, Bingwen
Abstract: In order to effectively evaluate the reactive power support capability of new energy stations, an evaluation system is established with the high voltage ride through(HVRT) capability, low voltage ride through (LVRT) capability and reactive power support capability selected as the evaluation index. And then, a comprehensive evaluation method to effectively evaluate the transient reactive support capability of new energy stations is proposed in this paper. The weight of a single index was determined by the coefficient of variation method and then the comprehensive evaluation index was determined based on TOPSIS(Technique for Order Preference by Similarity to an Ideal Solution). Finally, the rationality and effectiveness of the proposed evaluation method are verified by the measured data of a wind farm.